DEVELOPMENT OF DIE-CASTING MOLDING PRODUCTION TECHNOLOGY - V. N. Kuzmich; D. A. Moiseichik (Литьë и металлургия)
The main details of foundry equipment are developed. Analysis of the process of filling and hardening of casting “Transducer case” is carried out on the basis of methods of mathematic modeling of foundry processes.